An inside view of the CAP reform process explaining the MacSharry, Agenda 2000, and Fischler reforms - Cunha, Arlindo; Swinbank, A. (Alan) (Oxford : Oxford University Press, 2011)
From its formation in the 1960s through to 1992, the EU's Common Agricultural Policy (CAP) was almost immune to change. With the benefit of Arlindo Cunha's insider's knowledge, this book delves into the mysteries of the policy-making process by assessing the MacSharry, Agenda 2000, and Fischler reforms to the CAP.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Agricultural subsidies -- European Union countries